Penanggulangan Praktek Perundungan pada Amal Usaha Muhammadiyah (AUM) Bidang Pendidikan di PCM Socah Bangkalan - Noor Hasan, Dony Burhan; Fitroh, Siti Fadjrayana Fitroh; Endriyati, Enni Endriyati; Hisani, Nurul Hisani (Keris: Journal of Community Engagement, 2025)
One phenomenon that really attracts our adult attention in the world of education is bullying. Every year there are always new cases of student behavior which is categorized as deviant behavior, whether carried out deliberately with the intention to weaken the victim, humiliating, and carried out repeatedly so that bullying behavior is considered frightening and commonplace among students. Muhammadiyah, as the oldest religious community organization in Indonesia, has made many contributions to this nation in various fields. Of the many business charities initiated and owned by this association, this is a charity business in the field of education. It is recorded that Muhammadiyah has established many educational institutions in almost all regions of Indonesia totaling 3,334 with details of 1,904 elementary schools, 1,128 junior high schools, 558 high schools, 554 vocational schools, and 172 tertiary institutions consisting of 83 universities, 28 institutes, 54 high schools, 6 polytechnics and 1 academy. This shows that the problem of bullying or bullying is certainly also a classic problem faced by this organization. Therefore, various kinds of efforts are needed in order to overcome and minimize the occurrence of bullying in schools or educational institutions under the auspices of the Muhammadiyah Association. The efforts carried out in this community service program include: outreach about bullying, the trigger factors and its impact on students, and the preparation of a curriculum to create a child-friendly school and eliminate bullying in the school environment. Furthermore, the establishment of a "Character House" was initiated to handle various kinds of actions and impacts of bullying, aimed at victims and perpetrators of bullying.